2016
DOI: 10.1039/c6cp01841f
|View full text |Cite
|
Sign up to set email alerts
|

High-coverage stable structures of 3d transition metal intercalated bilayer graphene

Abstract: Alkali-metal intercalated graphite and graphene have been intensively studied for decades, where alkali-metal atoms are found to form ordered structures at the hollow sites of hexagonal carbon rings. Using first-principles calculations, we have predicted various stable structures of high-coverage 3d transition metal (TM) intercalated bilayer graphene (BLG) stabilized by the strain. Specifically, with reference to the bulk metal, Sc and Ti can form stable TM-intercalated BLG without strain, while the stabilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…To further evaluate the dopant distribution and relative structural stability of Mn 4+ -doped Cs 2 SiF 6 , we performed theoretical calculations on the 2 × 2 × 2 supercell of Cs 2 SiF 6 with one to four Si 4+ ions replaced by corresponding Mn 4+ ions. To describe it, we have calculated the formation enthalpy Δ H ( x ) as , ,where E x , E 1 , and E 0 are the total energies with a coverage of x , 1, and 0. Herein, x represents the value of the ion numer ratio of Mn 4+ to Si 4+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further evaluate the dopant distribution and relative structural stability of Mn 4+ -doped Cs 2 SiF 6 , we performed theoretical calculations on the 2 × 2 × 2 supercell of Cs 2 SiF 6 with one to four Si 4+ ions replaced by corresponding Mn 4+ ions. To describe it, we have calculated the formation enthalpy Δ H ( x ) as , ,where E x , E 1 , and E 0 are the total energies with a coverage of x , 1, and 0. Herein, x represents the value of the ion numer ratio of Mn 4+ to Si 4+ .…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the dopant distribution and relative structural stability of Mn 4+ -doped Cs 2 SiF 6 , we performed theoretical calculations on the 2 × 2 × 2 supercell of Cs 2 SiF 6 with one to four Si 4+ ions replaced by corresponding Mn 4+ ions. To describe it, we have calculated the formation enthalpy ΔH(x) as 42,43…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The C-C and C-TM equilibrium bond distances and d of the other BLG-TM layer materials are in agreement with the previous computational results. 31,33,34 The intercalation distances (d) in both the BLG-TM and bulk-BLG-TM are Figure 5 and the trend is similar for the bilayer and bulk analogs. To estimate the likehood of the synthesis of these materials, we have calculated the binding energy (ΔE b ) of both systems, BLG-TM and bulk-BLG-TM.…”
Section: Resultsmentioning
confidence: 69%
“…The C-C and C-TM equilibrium bond distances and d of the other BLG-TM layer materials are in agreement with the previous computational results. 31,33,34 The intercalation distances (d) in both the BLG-TM and bulk-BLG-TM are -5 4…”
Section: Resultsmentioning
confidence: 99%
“…A theoretical investigation of BLG intercalated with Cr was carried out using DFT, which found that BLG-Cr layer material is ferromagnetic. [27] Using first-principles calculations, Liao et al [30] investigated various stable BLG structures intercalated with Sc and Ti. They found that the strain was important for the stability of high-coverage TM in BLG.…”
Section: Introductionmentioning
confidence: 99%